2018
DOI: 10.1371/journal.pone.0198411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fludioxonil, propolis and black seed oil application on the postharvest quality of “Wonderful” pomegranate

Abstract: Pomegranate fruit consumption has increased rapidly throughout the world, mainly because of its medical and nutritive attributes. Thus, considerable commercial and scientific interest exists in prolonging its postharvest life with non-chemical applications as much as possible to meet the year-round demand for this fruit. The present work aimed to study the effects of black seed oil (0.1% and 0.5%), propolis (0.01% and 0.1%) and fludioxonil (0.06%), with and without modified atmosphere packaging (MAP), on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…The ability of MAP to prevent weight loss was previously reported by several researchers for various fruits (Caleb et al, 2013;Dhall et al, 2012;Kahramano glu et al, 2018) and for cucumber fruits (Manjunatha and Anurag, 2014;Wang and Qi, 1997). In addition, application of PEx and LO was found to reduce weight loss of cucumber fruit, in agreement with previous studies carried out on different fruits (Kahramano glu 2019;Kahramano glu et al, 2018;€ Ozdemir et al, 2010;Prakash et al, 2015;Zahid et al, 2013). Results also suggest that the combination of MAP with LO or PEx better prevents weight loss.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The ability of MAP to prevent weight loss was previously reported by several researchers for various fruits (Caleb et al, 2013;Dhall et al, 2012;Kahramano glu et al, 2018) and for cucumber fruits (Manjunatha and Anurag, 2014;Wang and Qi, 1997). In addition, application of PEx and LO was found to reduce weight loss of cucumber fruit, in agreement with previous studies carried out on different fruits (Kahramano glu 2019;Kahramano glu et al, 2018;€ Ozdemir et al, 2010;Prakash et al, 2015;Zahid et al, 2013). Results also suggest that the combination of MAP with LO or PEx better prevents weight loss.…”
Section: Discussionsupporting
confidence: 90%
“…Results also suggest that the combination of MAP with LO or PEx better prevents weight loss. Kahramano glu et al (2018) and Kahramano glu (2019) presented similar results for different crops with PEx, LO, and black seed oil treatments.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In Cyprus some authors have tested the use of propolis from Cyprus on the post-harvest quality of pomegranate with/without modified atmosphere packaging (MAP) and have found that propolis, not only, significantly influence the maintenance of fruit, weight, juice content and visual quality and marketability, but also controlled gray mold development and slowed the occurrence of chilling injury. [278] Northern African Coast…”
Section: Application In Food Industries Fieldmentioning
confidence: 99%